1998
DOI: 10.1111/j.2044-8341.1998.tb01374.x
|View full text |Cite
|
Sign up to set email alerts
|

Guilt proneness and expressed emotion in relatives of patients with schizophrenia or related psychoses

Abstract: Our analyses indicate that relatives' guilt proneness may be a determinant of their criticism, hostility and emotional overinvolvement towards a schizophrenic family member. This personality trait should be taken into account in family work which aims at modifying relatives' expressed emotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
0
24
2
3
Order By: Relevance
“…However, Scazufca and Kuipers (1998) have reported that EE remained constant in two-thirds of the family members recruited and changes in EE levels in the families were predicted by changes in family burden and extent of contacts between patient and family within a 9-month follow-up period. Bentsen et al (1998) also found that the three domains of EE (criticism, hostility and emotional over-involvement) are associated with patient and family variables such as patient's functioning and caregiver's emotional state. Therefore, EE has often been used as a measure of treatment outcome for schizophrenic patients.…”
Section: Literature Reviewmentioning
confidence: 81%
“…However, Scazufca and Kuipers (1998) have reported that EE remained constant in two-thirds of the family members recruited and changes in EE levels in the families were predicted by changes in family burden and extent of contacts between patient and family within a 9-month follow-up period. Bentsen et al (1998) also found that the three domains of EE (criticism, hostility and emotional over-involvement) are associated with patient and family variables such as patient's functioning and caregiver's emotional state. Therefore, EE has often been used as a measure of treatment outcome for schizophrenic patients.…”
Section: Literature Reviewmentioning
confidence: 81%
“…Perhaps the low-criticism relatives have simply reached the insight, either through empathy or experience, that coercive criticism does not work for the behaviours associated with psychosis. If, as attachment theory suggests, a normal reaction to loss involves coercive anger or criticism, we might expect a resolution of EOI behaviour to criticism over a period of time, once some issues of guilt and insecurity [27] in the carer had been worked through. Using this model, we would expect that in most cases, the high EOI of relatives should gradually resolve into high-CC or low-EE responses and we should seldom see a low-EE relative change status to a high-EOI relative except where there is an acute deterioration in the patient's condition.…”
Section: Discussionmentioning
confidence: 98%
“…Because guilt encourages reparative behaviors, relatives who feel excessively blameworthy regarding the patient's illness may resort to over-involvement or sacrificing conduct in order to mend behaviors and events for which they feel guilty. Indeed, Bentsen et al (1998) found that high levels of guilt-proneness, or a tendency to engage in self-blame, were positively associated with the EOI component of EE. Thus guilt may induce reparative behaviors but simply the wrong kinds (those that are maladaptive).…”
Section: Introductionmentioning
confidence: 99%
“…Following Bentsen et al (1998) who stated that “self-blame is an equivalent of guilt,” the current study uses guilt and self-blame interchangeably. Shame and guilt/self-blame are both self-evaluative emotions (Tracy and Robins, 2006).…”
Section: Introductionmentioning
confidence: 99%